Etiology Based on Clinical Manifestation of Acute Diarrhea Incidence of Children Hospitalized in Dr. Soetomo General Hospital Surabaya Period 2011-2013 - Ashfahani Imanadhia; IGM Reza Gunadi Ranuh; Djohar Nuswantoro (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2019)
Introduction: Diarrhea is one of the most common causes of morbidity and mortality of children worldwide, especially in developing countries. Acute diarrhea can occur from a large number of causes. We aim to describe the clinical manifestation characteristics of acute diarrhea on pediatric patients that are presented to the hospital.Methods: A cross-sectional study from all pediatric patients treated in Dr. Soetomo General Hospital Surabaya in 2011-2013.Age, gender, nutritional status, length of hospital stay, duration of breastfeeding, clinical signs and symptoms, as well as laboratory results collected and analyzed descriptively.Results: One hundred and fifty patients were included with characteristics of male(54%), infant (55.3%)with a mean age of 6-7 month. History of being exclusively breastfed(54%) and lack of nutrition(48%). Vomiting is mostly present (72.7%) and commonly come with a combination of two symptoms (42%) which were vomiting and fever. Mild to severe dehydration degree could be found on the patient who had vomiting, seizure, and fever. The most length of stay was frequently >72 hours. The occurrence of acute diarrhea on a child who was treated in Dr. Soetomo General Hospital Surabaya is dominated by vomiting and it could be inferred that the most acute diarrhea has a tendency of being caused by a virus, where liquid acute diarrhea without blood, mucus, or fever is found.Conclusion: The etiology of acute diarrhea is mostly caused by viruses and symptoms dominated by a combination of vomiting, fever, and diarrhea without blood caused by villi damage.